The boyfriend candidate - Winstead, Ashley (Graydon House, 2023)
After a freak lightning storm which interrupts her first one-night stand, shy librarian Alexis Stone is thrust into the spotlight when photographers catch her in the arms of the hotshot candidate running for governor of Texas who, to squelch rumors, demands she pretends to be his girlfriend until election day.